Reassortment of pandemic H1N1/2009 influenza A virus in swine - Vijaykrishna, D. (2010)
The emergence of pandemic H1N1/2009 influenza demonstrated that pandemic viruses could be generated in swine. Subsequent re-introduction of H1N1/2009 to swine has occurred in multiple countries. Through systematic surveillance of influenza viruses in swine from a Hong Kong abattoir, we characterize a reassortant progeny of H1N1/2009 with swine viruses. Continued reassortment of H1N1/2009 with swine influenza viruses could produce variants with transmissibility and altered virulence for humans. Global systematic surveillance of influenza viruses in swine is warranted.